How to Avoid Middle-Income Traps? : Evidence from Malaysia - Flaaen, Aaron; Ghani, Ejaz; Mishra, Saurabh (World Bank, Washington, DC, 2015)
Malaysias structural transformation from low to middle income has made it one of the most prominent manufacturing exporters in the world. However, in the competitive global economy, like many other middle-income economies, it is sandwiched between low-wage economies on one side and more innovative advanced economies on the other. What can Malaysia do? Does Malaysia need a new growth strategy?